2011
DOI: 10.2119/molmed.2011.00176
|View full text |Cite
|
Sign up to set email alerts
|

The p53 Upregulated Modulator of Apoptosis (PUMA) Chemosensitizes Intrinsically Resistant Ovarian Cancer Cells to Cisplatin by Lowering the Threshold Set by Bcl-xL and Mcl-1

Abstract: Ovarian cancer is the number one cause of death from gynecologic malignancy. A defective p53 pathway is a hallmark of ovarian carcinoma. The p53 mutation correlates significantly with resistance to platinum-based chemotherapy, early relapse and shortened overall survival in ovarian cancer patients. PUMA (p53 upregulated modulator of apoptosis), a BH3-only Bcl-2 family protein, was recently identified as a transcriptional target of p53 and a potent apoptosis inducer in various cancer cells. In this study, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…One of the potential explanations might be the p53 status since only Capan-2 cells express wild type p53, while all other tested PC cell lines express mutated p53. Differences in p53 status might influence the efficacy of UMI-77 in Capan-2 cell line as it is known that p53 activates the transcription of Puma and Noxa, thus shifting the balance of the Bcl-2 family towards pro-apoptotic members (3133). p53-mediated induction of Puma might enhances the sensitivity of Capan-2 cells by lowering the threshold set by Bcl-xL, which is highly expressed in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…One of the potential explanations might be the p53 status since only Capan-2 cells express wild type p53, while all other tested PC cell lines express mutated p53. Differences in p53 status might influence the efficacy of UMI-77 in Capan-2 cell line as it is known that p53 activates the transcription of Puma and Noxa, thus shifting the balance of the Bcl-2 family towards pro-apoptotic members (3133). p53-mediated induction of Puma might enhances the sensitivity of Capan-2 cells by lowering the threshold set by Bcl-xL, which is highly expressed in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…These included BBC3, which encodes PUMA, a p53 transcriptional target also involved in the response to endoplasmic reticulum stress induced by vinka alkaloids, including vinorelbine. 34,56,57 Sublethal exposure of both cell lines to cisplatin plus vinorelbine increased the expression of TFPI2, a gene encoding the protein tissue factor pathway inhibitor 2 (Fig. 4).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study showed that PUMA could chemosensitize ovarian cancer cells [2], However, the action mechanism remains elusive. A previous report has shown that PUMA overexpression induces ROS generation in colorectal cancer cells [26].…”
Section: Discussionmentioning
confidence: 99%